Comparison of Growth of Carps Fed on Salvinia based Feed and Conventional Feed* - Shivananda Murthy, H.; Devaraj, K.V. (Fishery Technology, 2025)
Utility of floating aquatic weed Salvinia in the feed for grass carp and common carp fingerlings has been studied. Both Salvinia based feed (SF) and control feed (CF) was fed at the rate of 5% of the body weight of fish in an experiment conducted for 112 days in 20 m2 cement cisterns with triplicates for each treatment. Statistical analysis of results indicated that there was no significance at 5% level between the fishes fed by Salvinia based feed, and control feed on their growth.